(untitled) (Wire Insights: Journal of Innovation Insights, 2026)
The article analyzes the new requirements for the process of training future teachers in the context of the continuous modernization of the education system, the widespread introduction of electronic learning technologies, and the use of open interactive and multimedia educational resources. The purpose of the study is to scientifically substantiate the need to form project competence of future teachers in the educational environment of a higher educational institution and to identify important pedagogical aspects of this process. The article highlights the importance of modeling, forecasting and designing students’ educational and cognitive activities, as well as planning the trajectory of personal professional development, in the professional activities of future teachers. Based on the requirements of regulatory legal acts on education policy, project competence is interpreted as an important component of modern pedagogical professional training.